No association between C-reactive protein and depressive symptoms among the middle-aged and elderly in China: Evidence from the China Health and Retirement Longitudinal Study - Zhang, Lin (Medicine (Baltimore), 2018)
The depressive symptoms have been associated with increased disabilities, and the depressive symptoms-related elevation of high C-reactive protein (CRP) has been proposed as a possible mechanism. We examined the relations between CRP and depressive symptoms among the middle-aged and elderly in China. A longitudinal sample of the middle-aged and elderly (4404 men and 5055 women) who were interviewed in the 2011 China Health and Retirement Longitudinal Study was used. A multivariate logistic regression analysis was used to examine the effects of sociodemographic characteristics, lifestyle, activity status, physical exercise, systolic blood pressure, low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglycerides, body mass index (BMI), and CRP levels on depressive symptoms. The mean age in the study was 60.26 years [standard deviation (SD) ± 9.25; 46.56% men]. The mean CPR level was 2.79 mg/L (range, 0.01–178.10; SD ± 7.80). Depression scores ranged from 0 to 30 with a mean 8.65 (SD ± 6.33). The prevalence of depressive symptoms was 38.49% in the total population, 31.04% in men and 44.99% in men. Compared with baseline CRP levels (≤1.00 mg/L), the depressive symptoms are only weakly correlated with CRP levels among women [CRP 1.01–3.00 mg/L: odds ratio (OR) = 0.85, 95% confidence interval (CI) = 0.73–0.98; CRP 3.01–10.00 mg/L: OR = 1.25, 95% CI = 1.03–1.51; CRP >10 mg/L: OR = 1.41, 95% CI = 1.06–1.88]. After adjusting for age, education, marital status, hukou, residence, cigarette smoking, alcohol drinking, eating meals, activity status, major accidental injury, diseases, health status, physical exercise, systolic blood pressure, LDL, HDL, triglycerides, and BMI, depressive symptoms were not associated with subsequent high CPR levels among the middle-aged and elderly (CRP 1.01–3.00 mg/L: OR = 0.93, 95% CI = 0.83–1.03; CRP 3.01–10.00 mg/L: OR = 0.95, 95% CI = 0.82–1.10; CRP >10 mg/l: OR = 1.11, 95% CI = 0.88–1.39). Our data do not support an association between CRP and depressive symptoms in both middle-aged and elderly men and women among china.